Perancangan Website UMKM Labersa Petshop - Fauziah, Fauziah; Putri Wulandari; Zuhra Hisyafitri (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
In the current digital era, the advancement of information and communication technology has significantly transformed various aspects of life, including the business sector. Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia's economy, contributing to job creation and economic growth. However, many MSMEs still face challenges in leveraging technology to enhance their competitiveness. One effective way to improve the visibility and accessibility of MSMEs is through the utilization of websites. A website serves not only as an information medium but also as an effective marketing tool to reach a broader customer base. With a website, MSMEs can promote their products and services online, thereby increasing sales and expanding market share. Labersa Petshop, as an MSME operating in the pet product sales sector, has significant potential for further development by utilizing information technology. Nonetheless, there are still obstacles in management and marketing that can be addressed through effective web design. Therefore, our group initiated a Project-Based Learning (PBL) project focused on creating a website for Labersa Petshop. Through this project, we aim to provide tangible contributions to Labersa Petshop in developing their business while also offering practical experience for students in applying the knowledge acquired in their studies. This report is prepared as documentation of the processes and results obtained during the project implementation, as well as a learning resource for relevant parties.